Effects of platelets on extracellular traps of neutrophils in patients with systemic lupus erythematosus - I. A. Novikova; Z. V. Zubkova (Медицинская иммунология, 2021)
Platelets are central participants in hemostasis, and also contribute to the host inflammatory and immune responses. Platelets are known to have a direct effect on the formation of neutrophil extracellular traps. Moreover, the patients with systemic lupus erythematosus exhibit multidirectional disturbances in the functional activity of platelets and neutrophils. Changes in inflammatory and thrombotic events can be considered predictors for adverse clinical course in systemic pathology. The aim of present study was to evaluate the possible role of platelets in maintaining increased netosis in patients with systemic lupus erythematosus. Blood platelets and white blood cells from 29 patients with systemic lupus erythematosus (SLE) were subject to the study. We have registered the in vitro effects of platelets upon formation of extracellular traps by autologous neutrophils under the conditions of co-cultivation for 30 minutes (vital NETosis) and 150 minutes (suicidal NETosis), as well as the relationships between the platelet counts, their activity and the number of NETs observed. It was found that the severity and direction of the platelets effect upon NETosis in vitro cultures depends on the degree of activity of disease: in the 1st degree of SLE, the effect of platelets did not differ from healthy individuals, i.e., intact platelets suppress NETosis (p = 0.002), whereas ADP-induced patelets did not exert any effect); at the 2nd degree of activity, both intact and activated platelets increase NETotic activity (p = 0.03 and p = 0.04 for intact and activated platelets, respectively). In the patients with 3rd degree of the disease activity, platelets did not affect formation of NETs. Hyperactivation of platelets was detected in SLE patients, mostly pronounced in the cases with 2nd degree of activity. However, we have not revealed any significant relationships between the count of platelets, their functional activity (according to results of ADP-test aggregation), and the indexes of NETosis. At the same time, the counts of neutrophil extracellular traps in bloodstream depended on the concentration of C-reactive protein (r = 0.58; p = 0.02), the titer of autoantibodies (anti-SS-A and anti-SS-B) (r = 0.66; p = 0.04 and r = 0.76; p = 0.02, respectively), rheumatoid factor (r = 0.73; p = 0.007) and circulating immune complexes (r = 0.68; p = 0.02). The obtained results indicate that the platelet/neutrophil interactions are not the leading cause for increased NETs numbers in SLE, compared to significantly higher effects of soluble autoagressive factors.